Phytochemical screening of Prunus avium for its antioxidative and anti-mutagenic potential against DMBA-induced hepatocarcinogenesis - Saeed, Raakia Anam; Khan, Muhammad Issa; Butt, Masood Sadiq; Faisal, Muhammad Naeem (Frontiers in Nutrition, 2023)
Scope Prunus avium fruit is the richer source of phenolics known to exert anticancer and anti-invasive activities. The study aimed at elucidating antiproliferative and chemo-preventive potential of sweet cherries (P. avium) against the in vivo hepatocarcinoma model. Methods and results The quantification of ultrasound-assisted extract (UAE) of P. avium depicted anthocyanins, ferulic acid, gallic acid, quercetin, syringic acid and p- and m-coumaric acids as major phytochemicals. The hepatocarcinoma (HCC) was induced in rats through intraperitoneal administration of DMBA (20 mg/kg B.W) once a week for the period of eight weeks. The intragastric administration of P. avium UAE, as cotreatment (500 mg/Kg B.W) to treatment group, significantly (p < 0.01) attenuated the raised serum alpha-fetoprotein (AFP), carcinoembryonic antigen (CEA), alanine aminotransferase (ALT), aspartate aminotransferase (AST), lactate dehydrogenase (LDH) as well as total oxidative stress (TOS) and enhanced total antioxidant capacity TAOC in contrast to diseased rats. Moreover, microscopic examination of hepatic tissues confirmed the pleomorphism, nests of neoplastic hepatocytes and necrosis in HCC-bearing rats as compared to extract-fed rats, where these necrotic changes were suppressed. Besides, qRT-PCR analysis of hepatic tissues demonstrated the higher mRNA expression of CHEK1, CHEK2 and P21/CDKN1α genes, while downexpression of ATM gene in extract fed rats, further denoting the anti-mutagenic potential. Conclusion Consequently, the polyphenol-rich sweet cherries UAE exhibited antiproliferative and chemo-preventive potential by reducing tumor biomarkers, serum transaminases and oxidative stress, as well as enhancing antioxidant status. It further upregulated the downstream targets of ATM signaling cascade.